My country, mine country : Indigenous people, mining and development contestation in remote Australia - Scambary, Benedict (Research monograph (Australian National University. Centre for Aboriginal Economic Policy Research), 2013)
Within the context of three mining agreements in North Australia this study considers Indigenous livelihood aspirations and their intersection with sustainable development agendas.